2011
DOI: 10.1108/17566261111169313
|View full text |Cite
|
Sign up to set email alerts
|

Proactive and reactive plots: narratives in entrepreneurial identity construction

Abstract: Purpose: The purpose of this paper is to offer a new perspective on entrepreneurial identity as a narrative construction, emerging in stories about entering the family business.Design/methodology/approach: The qualitative methodological approach involves an interpretative analysis of transcribed interviews, conducted in narrative style with 12 women from Swedish family businesses.Findings: By presenting entrepreneurial identity as a combination of two distinct narratives, the "passive" entrance into the family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 56 publications
(76 reference statements)
0
53
0
1
Order By: Relevance
“…women's engagement in business followed the same gendered pattern (Klyver 2011;Dalborg et al 2012;Bjursell and Melin 2011;Holmquist and Sundin 1990;Shane et al 1991;Kolvereid et al 1993;Ljunggren and Kolvereid 1996 In the first theme, we discuss studies that address how women's entrepreneurship is positioned in various contexts, such as the contexts of family, the economy, the media, and the welfare state. The second theme addresses government support for women's entrepreneurship.…”
Section: Findings: Nordic Research On Women's Entrepreneurshipmentioning
confidence: 99%
“…women's engagement in business followed the same gendered pattern (Klyver 2011;Dalborg et al 2012;Bjursell and Melin 2011;Holmquist and Sundin 1990;Shane et al 1991;Kolvereid et al 1993;Ljunggren and Kolvereid 1996 In the first theme, we discuss studies that address how women's entrepreneurship is positioned in various contexts, such as the contexts of family, the economy, the media, and the welfare state. The second theme addresses government support for women's entrepreneurship.…”
Section: Findings: Nordic Research On Women's Entrepreneurshipmentioning
confidence: 99%
“…This field of study is relevant because others have also concluded that increasing numbers of women are entering family businesses and taking up leadership positions (Barrett & Moores, 2009;Harveston et al, 1997). The move from the family context to the business context has an impact on the individual woman´s identity process (Bjursell & Melin, 2011).…”
Section: Gender Theory In Family Business Researchmentioning
confidence: 99%
“…In line with the diversity in family businesses and believing that theorising in entrepreneurship has much relevance for family business, there is a link between gender and entrepreneurship and gender and family businesses. Bjursell and Melin (2011) argue for a shift away from focussing on the entrepreneur as a masculine concept towards understanding entrepreneurship as a combination of the masculine and the feminine. They use stories about women entering the family business and offer a new perspective on entrepreneurial identity as a narrative construction.…”
Section: Gender Theory In Family Business Researchmentioning
confidence: 99%
See 2 more Smart Citations